The effectiveness of e-corporate governance: an exploratory study of internet voting at shareholders' annual meetings in France. Issue 4 (1st May 2020) - Abdennadher, Sonia; Cheffi, Walid
Abstract : Purpose: E-corporate governance or the use of technologies and information systems (ISs) in corporate governance, is still a subject that is too seldom addressed in business research. This paper is at the intersection between two fields of research (corporate governance and the management of ISs), which are interdependent in ways that are still unexplored. The paper analyzes the implications of internet voting (IV) at shareholders' annual meetings (SAM) for the corporate governance of listed companies in France, in particular for the relationship between executives and shareholders. Most of the studies that have dealt with IV at SAM have focused on techno-legal issues and were often conducted by business law researchers. The purpose of this paper is to investigate the implications of the new voting system through the prism of corporate governance. Design/methodology/approach: The authors proceeded by triangulation of methods. This qualitative study is based on observations, interviews and documentary analysis. It assessed the IV implications for both the issuing companies and the shareholders. Findings: The new voting system brings undeniable competitive advantage to the issuing company and facilitates shareholders' activism, yet it has serious risks both for the corporations and for certain categories of the shareholder. Interestingly, the authors propose an original and field-grounded typology that distinguishes the risks and benefits associated with IV in relation to executives' attitudes. Social implications: The paper shows that the resolving of identified deficiencies with IV development could contribute to the alignment of companies' interests with those of shareholders. Moreover, the study calls for policymakers to appoint an official body to regulate the practical implementation of the new system and to prevent its dissemination being held hostage to the executives' willingness. Originality/value: An original aspect of this research lies in the effective operationalization of the constructs of corporate governance effectiveness with a view to examining corporate governance as a set of technologically mediated practices. Moreover, this study emphasizes the key role of the construct of "executives' willingness" in facilitating/impeding IV diffusion. This underlies their attempts to reverse the corporate governance relationship.